THE QUALITY OFSUMBAWAHORSE MILKATROOM TEMPERATURE STORAGE - I Nengah Kerta Besung (Buletin Veteriner Udayana, 2017)
Research has been conducted to determine the quality of Sumbawa horse milk at room temperature storage. Each sample (of 5 horse) was divided into 5 cups Beaker and then stored at room temperature. Observations were made as many as 6 times to checked and tested on parameters including pH, alcohol, smell and a flavor test. This study uses a randomized block design (RBD), using 5 horses as a group, and time observations on days 0, 1st, 2nd, 3rd, 4th, and 5th as a treatment, so tested 30 samples. The results showed that the pH of milk has significantly (P>0,05) lower quality. On the alcohol test showed positive results and the test on the smell and flavor test shaved changes quality after the 2nd day. Of observations Sumbawa horse milk quality decrease very markedly decreased pH (P<0.01) on day 0 to day 1 and significantly (P<0.05) decreased from day 1 to day 2 but not significant (P>0.05) decreased from day 2 to day 3 during storage. Alcohol test resistance at Sumbawa horse milk increasingly distorted and react positively. On the smell and flavor test Sumbawa horse milk taste very significant (P<0.01) deviates smells during storage at room temperature begins 2nd day. To maintain the quality of Sumbawa horse milk should be stored no more than 2 days at room.